Stadtstrukturen in Kanada und den USA im Vergleich. Die Dialektik von Stadt und Gesellschaft - Helbrecht, Ilse (ERDKUNDE, 1996)
The notion of the North American city has been a valuable concept far European geographers. It allows far a constitutive outside and helps situate different pathways of urban development on an international scale. However, empirical data show significant differences between American and Canadian cities in terms of density, urban sprawl, and housing. Thus Canadian geographers reject the concept of a single North American city and conceptualize the Canadian city as a distinct entity. This paper presents macrostatistical data on American and Canadian cities and compares the role of the inner city, the extent of social polarisation, and the quality of urban life in Canada and the US. It is argued that the inner city location of urban elite areas and the gestalt of urban poverty playa crucial role in understanding the distinctiveness of the Canadian city. In conclusion the empirical findings are discussed within the broader context of the dialectics of cities and societies.